Invitrogen catalog 2000 now with Novex electrophoresis products. (Groningen, The Netherlands Invitrogen, 2000)
Introduces cloning and genetic engineering, exploring the technology and social issues involved and looking toward what the future might bring as it becomes possible to duplicate even human DNA.
Understanding the terms -- Learning through history -- Gene genies and clone arrangers -- What the future holds.
Includes index.
Includes appendix.
Keywords: Cloning -- Juvenile literature; Genetic engineering -- Juvenile literature; Cloning; Genetic engineering; Genetics